Diskresi Kepala Daerah Dalam Penetapan Penjabat Kepala Desa - Vella Graita Widyasari (Lentera Hukum, 2016)
Discretion is an authority owned by government officials in terms of performing an act that is deemed desperately needed by the community. The Government Administration Act Article 1 number 9 explains that discretion is a decision and action taken by government officials to overcome concrete problems which in the case of legislation provide a choice not to regulate, unclear, incomplete, and the existence of government stagnation. In terms of determining the position of the village head who had stopped and was dismissed the Law on Villages in 2014, stated that the replacement of the village head official was an interim official who was a civil servant in the regional government. This is deemed unclear in the regulations, besides being unclear or ambiguous, this rule has several judgments that will hamper the election of the acting village head. That way, the regional head who is obliged to still be able to carry out the duties of the public service and the application of the welfare state, thus can use the authority of discretion in terms of determining the village head official. The purpose of this discretion is done as a breakthrough and problem solver in society in general. The method of this research is juridical-normative. The approach used is the approach of legislation and conceptual approach. This is confirmed by the existence of the 1945 Constitution of the Republic of Indonesia opening of the fourth century, which states that every society needs to get welfare and elements of discretion which explains that discretion is aimed at public services, the public interest, and the needs of society. KEYWORDS: Head of Region, Discretion, Acting Head of Village.